2022
DOI: 10.1101/2022.12.12.520188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing habit learning in the human brain at the individual and group levels: a multi-modal MRI study

Abstract: The dual-process theory of action control postulates that there are two competitive and complementary mechanisms that control our behavior: a goal-directed system that executes deliberate actions, explicitly aimed toward a particular outcome, and a habitual system that autonomously execute well-learned actions, typically following an encounter with a previously associated cue. In line with dual-process theory, animal studies have provided convincing evidence for dissociable neural mechanisms, mainly manifested… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 143 publications
2
6
0
Order By: Relevance
“…This joins our general proposition that the expression of habits, especially when they are no longer adaptive, is a subtle effect and its stability is subject to a variety of factors. The observation that a subset of participants in the extensive training groups manifested sensitivity to outcome devaluation (which is in line with previous evidence 25,31,32 ) perhaps indicates that habit formation is not a unitary deterministic process. We therefore propose that acquiring large datasets is of great value to further establish the effects found here and explore other factors implicated in habit learning.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This joins our general proposition that the expression of habits, especially when they are no longer adaptive, is a subtle effect and its stability is subject to a variety of factors. The observation that a subset of participants in the extensive training groups manifested sensitivity to outcome devaluation (which is in line with previous evidence 25,31,32 ) perhaps indicates that habit formation is not a unitary deterministic process. We therefore propose that acquiring large datasets is of great value to further establish the effects found here and explore other factors implicated in habit learning.…”
Section: Discussionsupporting
confidence: 88%
“…Experimental habit induction in humans has constituted a significant hurdle for researchers in the field. Promising results of habit formation following extensive training were demonstrated in one study 30 (indexed by insensitivity to outcome devaluation), but a series of attempts were not successful in replicate those findings 25,31,32 . Other attempts targeting decreased sensitivity to outcome Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, perhaps the most basic demonstration of habit formation through prolonged training has yet to be reliably demonstrated. Only a single study has successfully demonstrated the shift in action control as a function of training duration (Tricomi et al, 2009 ) but those results have not been replicated thus far and have been challenged in multiple replication attempts (de Wit et al, 2018 ; Gera et al, 2022 ; Pool et al, 2022 ). This impedes our ability to understand the mechanisms underlying habit formation and the development of potential interventions, and has left the research of habit formation in humans far behind its animal counterpart.…”
Section: Introductionmentioning
confidence: 99%